ANALISIS PENGARUH INFLASI, TENAGA KERJA, IPM, DAN INFRASTRUKTUR JALAN TERHADAP PEREKONOMIAN PAPUA - Wardiningrum, Bertha Putri; Devia SS, Vietha (Journal of Development Economic and Social Studies, 2024)
Papua is located in the eastern part of Indonesia, which makes it one of the regions that require special attention for economic development. Compared to some other provinces in Indonesia, Papua Province is still experiencing a stage of growth. The aim of this study is to study how inflation, labor, human development index, and road infrastructure development affect the economic growth of Papua Province. This associative research uses quantitative analysis. In this study, the data analysis technique used is multiple regression analysis. This is done using secondary data, which is the time series of 2011–2022. The study found that inflation correlated positively and significantly with economic growth. Partially the labor variable has a positive and significant regression direction towards economic growth. The IPM variable has a significant influence with a negative regression direction and the road infrastructure has a negatively regression coefficient and has no significant impact on the economic growth of Papua Province. Inflation, labor, IPM, and road infrastructure have a significant impact on the economic growth of the Papua province simultaneously.